Cistanche deserticola polysaccharide attenuates osteoclastogenesis and bone resorption via inhibiting RANKL signaling and reactive oxygen species production. Issue 12 (3rd July 2018) - Song, Dezhi; Cao, Zhen; Liu, Zaibing; Tickner, Jennifer; Qiu, Heng; Wang, Chao; Chen, Kai; Wang, Ziyi; Dong, Shiwu; Xu, Jiake
Abstract : Osteoporosis is a metabolic disease characterized by osteopenia and bone microstructural deterioration. Osteoclasts are the primary effector cells that degrade bone matrix and their abnormal function leads to the development of osteoporosis. Reactive oxygen species (ROS) accumulation during cellular metabolism promotes osteoclast proliferation and differentiation, therefore, playing an important role in osteoporosis. Cistanche deserticola polysaccharide (CDP) possesses antitumor, anti‐inflammatory, and antioxidant activity. However, the impact of CDP on osteoclasts is unclear. In this study, tartrate‐resistant acid phosphatase staining, immunofluorescence, reverse transcription‐polymerase chain reaction, and western blot analysis were utilized to demonstrate that CDP inhibited osteoclastogenesis and hydroxyapatite resorption. In addition, CDP also inhibited the expression of osteoclast maker genes including Ctsk, Mmp9, and Acp5 and had no effect on receptor activator of nuclear factor κB (RANK) expression. Mechanistic analyses revealed that CDP increases the expression of antioxidant enzymes to attenuate RANKL‐mediated ROS production in osteoclasts and inhibits nuclear factor of activated T cells and mitogen‐activated protein kinase activation. These results suggest that CDP may represent a candidate drug for the treatment of osteoporosis caused by excessive osteoclast activity. Abstract : CDP suppresses RANKL‐induced ROS production, as well as NFATc1 and MAPK activation, hence inhibits osteoclastogenesis.